PENGARUH PRODUK, LOKASI, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN CLUSTER VICTORIA (STUDI KASUS PT. ARTA BUANA SAKTI) - Bastian, Asep Ferry; Qori, Fitra Kalfi; Sukaesih, Imas (Universitas Islam Syekh-Yusuf, 2021)
Abstract This study aims to determine the effect of product, location, promotion on purchasing decisions in the Victoria cluster, a case study at PT. Arta Buana Sakti located in Tangerang. The research method of this research is quantitative with associative (causal) method. Population size using a limited population. For the determination of the research population, those who have purchased the Victorian cluster unit with a total of 240 units are already inhabited. To get the sample of this research using probability sampling method with simple random sampling technique, the formula used is slovin and get 71 respondents. Using a Likert scale measurement instrument. The results showed that partially the product had an effect on the purchasing decision of the Victoria cluster, partially the location had no effect on the purchasing decision of the Victoria cluster, partially the promotion affected the purchasing decision of the Victoria cluster, simultaneously product, location, promotion had an effect on the purchasing decision of the Victoria cluster. Keywords: Product, Location, Promotion, Purchase Decision.